Temperature-mediated biosynthesis of the phytotoxin phaseolotoxin by Pseudomonas syringae pv. phaseolicola depends on the autoregulated expression of the phtABC genes - Virolle, Marie-Joelle; Aguilera, Selene; Alvarez Morales, Ariel; Murillo, Jesús; Hernández Flores, José Luis; Bravo, Jaime; De la Torre Zavala, Susana (2017)
Abstract Pseudomonas syringae pv. phaseolicola produces phaseolotoxin in a temperature dependent manner, being optimally synthesized between 18˚C and 20˚C, while no detectable amounts are present above 28˚C. The Pht cluster, involved in the biosynthesis of phaseolotoxin, contains 23 genes that are organized in five transcriptional units. The function of most of the genes from the Pht cluster is still unknown and little information about the regulatory circuitry leading to expression of these genes has been reported. The purpose of the present study was to investigate the participation of pht genes in the regulation of the operons coded into the Pht cluster. We conducted Northern blot, uidA fusions and reverse transcription-PCR assays of pht genes in several mutants unable to produce phaseolotoxin. This allowed us to determine that, in P. syringae pv. phaseolicola NPS3121, genes phtABC are essential to prevent their own expression at 28˚C, a temperature at which no detectable amounts of the toxin are present. We obtained evidence that the phtABC genes also participate in the regulation of the phtD, phtM and phtL operons. According to our results, we propose that PhtABC and other Pht product activities could be involved in the synthesis of the sulfodiaminophosphinyl moiety of phaseolotoxin, which indirectly could be involved in the transcriptional regulation of the phtA operon.